Analysis of Coverage of Health Services of Health Centers During The Covid-19 Pandemic in Aceh Besar District - Nurul Hayati; Maidar Maidar; Aulina Adamy (Universitas Syiah Kuala, 2018)
Quality basic health services in accordance with SPM (Minimum Service Standards) including promotive, preventive, screening , curative and rehabilitative activities are provided thoroughly to the community, groups and individuals both inside and outside the building, but experiencing various obstacles during the Covid pandemic. -19. This study aims to determine whether there is a difference between the coverage of health services before and during the pandemic, as well as how the management of the Head of Puskesmas and/or program managers on the achievement of MSS coverage. This study used a mixed method method, which combines research quantitative and qualitative conducted in 28 Puskesmas in Aceh Besar District with a sample of 336 respondents. The results showed that there were differences in service coverage for primary education age and services for people suspected of tuberculosis before and during the pandemic (P0.05), there was no difference in the coverage of health services for pregnant women, maternity mothers, newborns, toddlers, productive age. , elderly people, people with hypertension, people with diabetes, severe mental disorders and people at risk of HIV before and during the Covid-19 pandemic (p0.05). The leadership management of the head of the Puskesmas and program managers on the differences in the achievement of the SPM (Minimum Service Standards) coverage is quite good, including planning, program analysis, identification of problems and constraints, innovation and performance assessment of the puskesmas.